Lignin: a valuable feedstock for biomass pellet - Sujan, SMA; Kashem, MA; Fakhruddin, ANM (Bangladesh Journal of Scientific and Industrial Research, 2020)
Pelletization and briquettization have been extensively used for mass and energy densification of biomass. As the demand for pellets increases, the biorefinery waste lignin can be used with the conventional raw materials for pellet preparation. Sugarcane bagasse (20-40 mesh) is treated with NaOH (8% & 16%) for bioethanol production and obtained lignin is used to prepare pellet along and with sugarcane bagasse (SB). SB, Lignin1 (8% NaOH treated SB), Lignin2 (16% NaOH treated SB) and various composition of SB and Lignin1 were used to produce pelletswith different applied pressures (5kN, 10kN, 15kN and 20kN). Pellet density and heating value were gradually increase with the applied pelletization pressure. Among the samples Lignin1 showed highest heating value at 20kN (3581.54 kcal/kg). Results revealed that 5kN is enough to produce pellet from different composition of SB and Lignin1 and the pellet composition of SB (40%) and Lignin1(60%) showed the highest heating value (3456.21 kcal/kg). Bangladesh J. Sci. Ind. Res.55(1), 83-88, 2020